Trace metal concentrations in the muscle of seven marine species: Comparison between the Gulf of Lions (North-West Mediterranean Sea) and the Bay of Biscay (North-East Atlantic Ocean). (October 2018) - Mille, Tiphaine; Cresson, Pierre; Chouvelon, Tiphaine; Bustamante, Paco; Brach-Papa, Christophe; Bruzac, Sandrine; Rozuel, Emmanuelle; Bouchoucha, Marc
Abstract: Concentrations of 6 trace metals (Ag, Cd, Cu, Ni, Pb, Zn) in the muscle of 2 sharks ( Galeus melastomus and Scyliorhinus canicula ), 4 teleosts ( Helicolenus dactylopterus, Lepidorhombus boscii, Micromesistius poutassou and Phycis blennoides ) and 1 crustacean ( Nephrops norvegicus ) were compared between the Bay of Biscay (Atlantic Ocean) and the Gulf of Lions (Mediterranean Sea). Although average concentrations and the trace element pollution index were generally higher in the Gulf of Lions, significant differences between the two ecosystems were only found for Zn for Helicolenus dactylopterus, and for Ag and Cu for the crustacean N . norvegicus . Moreover, some relationships between trophic level or size and metal concentrations were found for these two species. The absence of clear pattern may result from the blurring effect of contamination and excretion that may act differentially for all species and all elements. Highlights: Low concentrations of trace metals in the muscle tissue for all studied marine species Absence of clear patterns for all studied species and elements Metal concentrations were mainly higher in the Gulf of Lions than in the Bay of Biscay.